The Influence of Leadership and Work Motivation on Employee Performance at PT. Adira Finance Palopo - Salju Salju; M. Risal; Kamaruddin Kamaruddin (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
Every company wants excellent development in the business it manages. Success can be influenced by how well the performance is shown. Many factors can improve employee performance, such as leadership, work motivation, and other factors. This study aims to determine the effect of leadership and work motivation on employee performance at PT. Adira Finance Palopo with a sample of 89 respondents. The results showed that leadership had a positive and significant effect on employee performance. Employee motivation has a positive and significant influence on employee performance. Simultaneously leadership and work motivation have a significant effect.